1991
DOI: 10.1128/aem.57.3.875-878.1991
|View full text |Cite
|
Sign up to set email alerts
|

Viable but nonculturable bacteria in drinking water

Abstract: Klebsiella pneumoniae, Enterobacter aerogenes, Agrobacterium tumefaciens, Streptococcus faecalis, Micrococcus flavus, Bacillus subtilis, and Pseudomonas strains L2 and 719 were tested for the ability to grow and maintain viability in drinking water. Microcosms were employed in the study to monitor growth and survival by plate counts, acridine orange direct counts (AODC), and direct viable counts (DVC). Plate counts dropped below the detection limit within 7 days for all strains except those of BaciUus and Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(90 citation statements)
references
References 13 publications
4
85
0
1
Order By: Relevance
“…The reasons why the plating efficiency of pelagic bacteria is so low are unknown. Colwell and colleagues have proposed that stress of the ocean environment may render the bacteria unculturable while remaining viable [21,22]. We hypothesize that low plating efficiency of the dominant bacteria (as in our study) may have been caused through lysis by bacteriophages entering lytic phase upon shift-up of bacteria on the culture medium [23].…”
Section: Resultsmentioning
confidence: 65%
“…The reasons why the plating efficiency of pelagic bacteria is so low are unknown. Colwell and colleagues have proposed that stress of the ocean environment may render the bacteria unculturable while remaining viable [21,22]. We hypothesize that low plating efficiency of the dominant bacteria (as in our study) may have been caused through lysis by bacteriophages entering lytic phase upon shift-up of bacteria on the culture medium [23].…”
Section: Resultsmentioning
confidence: 65%
“…However, aggregates were never observed under the microscope in the leaf homogenate used for plate counts. VBNC bacteria have previously been detected in microbiologically-controlled systems such as autoclaved or filtered water (Byrd et al 1991;Besnard et al 2000b) and in sterilized irradiated seeds (Pedersen and Leser 1992;Grey and Steck 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This state has been described as viable but non-culturable (VBNC). Certain enteric bacteria can retain their pathogenicity whilst VBNC [5,6]. A recent study showed that intact S. typhimurium cells reside in non-sterile soil for long periods of time in spite of apparent rapid die-o¡ according to viable counts on selective agar [7].…”
Section: Introductionmentioning
confidence: 99%